The inversion of geoelectrical data for hydrogeological applications in crystalline basement areas of Nigeria (1997)
A methodology is presented for the inversion of two-dimensional (2-D) geoelectrical data for solving hydrogeological problems in crystalline basement areas. The initial step entails compiling an earth model using all available geological, borehole and geophysical information. This model then served as the input to a 2-D inversion algorithm based on the Simultaneous Iterative Reconstruction Technique (SIRT). The algorithm tries to find a model that is as close as possible to the starting model. To demonstrate the usefulness of this procedure, two field examples from Nigeria, conducted as part of a borehole siting programme, are described. In the first example, borehole information regarding the thickness of the weathered zone overlying a gneissic bedrock was used to constrain the 1-D inversion of sounding data and the model thus compiled was used as the starting model for 2-D inversion. In the second example, only sounding information was used to determine the starting model. If the starting model has incorporated all the available information as constraints, it is generally possible to compute a model that not only fits the measured data but is also a good approximation of the subsurface geology, more so when several 2-D models can fit the same set of field measurements on account of the limitations posed by equivalence